Chiral Ligands Derived from Monoterpenes: Application in the Synthesis of Optically Pure Secondary Alcohols via Asymmetric Catalysis. Issue 4 (30th October 2014) - El Alami, Mohammed Samir Ibn; El Amrani, Mohamed Amin; Agbossou‐Niedercorn, Francine; Suisse, Isabelle; Mortreux, André
Abstract The preparation of optically pure secondary alcohols in the presence of catalysts based on chiral ligands derived from monoterpenes, such as pinenes, limonenes and carenes, is reviewed. A wide variety of these ligands has been synthesized and used in several catalytic reactions, including hydrogen transfer, CC bond formation via addition of organozinc compounds to aldehydes, hydrosilylation, and oxazaborolidine reduction, leading to high activities and enantioselectivities.